AN ANALYSIS OF JOURNALISTIC ETHICS IN THE DIGITAL AGE: A CASE STUDY ON ETHICAL PRACTICES IN DIGITAL MEDIA - Mayangsari; Abdul Wahid; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This study explores how digital media apply journalistic ethics and identifies key ethical challenges in the digital age. Using a qualitative case study approach, the research focuses on Beritakota Makassar, Media Sulsel, and Herald Sulsel. Data were gathered through interviews with journalists and editors, and document analysis.The results show that digital media uphold ethical principles such as independence, accuracy, verification, and professionalism. However, they also face challenges including the spread of fake news, pressure for speed, social media influence, and monetisation demands. Strengthening verification and promoting digital literacy are essential responses.This research offers insights into ethical practices in digital journalism and practical recommendations to support media integrity and public trust.